2019
DOI: 10.1002/jor.24193
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic proteoglycans can molecularly engineer early osteoarthritic cartilage in vivo

Abstract: Biomimetic proteoglycans (BPGs) have the potential to treat osteoarthritis (OA) given that these molecules mimic the structure and properties of natural proteoglycans, which are significantly reduced in OA. We examined the effects of BPGs injected into the intra-articular space in an in vivo OA rabbit knee model and evaluated the effect on histological response, joint friction, and BPG distribution and retention. Rabbits underwent ACL transection to create an arthritic state after 5 weeks. OA rabbits were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…In accordance with the presented data, biglycan has been previously described to have a mainly pericellular localization in healthy cartilage 32 . Recently, Phillips et al 42 showed that intra‐articular injected biomimetic proteoglycans are capable of diffusing into OA affected cartilage and being deposited into the pericellular region of the chondrocytes. Complexes of biglycan with other small proteoglycans such as matrilin‐1 and decorin have been indicated to act as a link between collagen type VI microfibrils and the extracellular components aggrecan and collagen type II 43 .…”
Section: Discussionsupporting
confidence: 88%
“…In accordance with the presented data, biglycan has been previously described to have a mainly pericellular localization in healthy cartilage 32 . Recently, Phillips et al 42 showed that intra‐articular injected biomimetic proteoglycans are capable of diffusing into OA affected cartilage and being deposited into the pericellular region of the chondrocytes. Complexes of biglycan with other small proteoglycans such as matrilin‐1 and decorin have been indicated to act as a link between collagen type VI microfibrils and the extracellular components aggrecan and collagen type II 43 .…”
Section: Discussionsupporting
confidence: 88%
“…BPG10 consists of a ∼10 kDa synthetic PAA core, decorated with ∼5−7 CS-GAG bristles (Figure 1a). The focus of BPG10 here was due to its capability of effectively diffusing into cartilage following intra-articular injection into rabbit knees in vivo 34 or after 24 h incubation of human or bovine explants in BPG10 aqueous solution in vitro. 35 Also, similar to aggrecan, BPG10 exhibits the "bottlebrush" architecture, with CS-GAGs packed at 3−4 nm spacing along the PAA core, 31 comparable to the 2−3 nm spacing of CS-GAGs along aggrecan core protein, 36 indicating that BPG10 may partially mimic the biophysical characteristics of native aggrecan.…”
Section: Resultsmentioning
confidence: 99%
“…We (Phillips et al, 2018;Prudnikova et al, 2017;Prudnikova et al, 2018;Sarkar, 2011;Sarkar et al, 2017;Sarkar, Lightfoot-Vidal, Schauer, Vresilovic, & Marcolongo, 2012) and others (Bernhard & Panitch, 2012;Place, Kelly, & Kipper, 2014;Sharma, Panitch, & Neu, 2013;Sharma, Vazquez-Portalatin, Calve, & Panitch, 2016) have been investigating mimics to proteoglycans. We designed, synthesized and characterized biomimetic proteoglycans (BPGs) that mimic the molecular architecture and physical properties of natural proteoglycans.…”
Section: Hartmannmentioning
confidence: 99%
“…In a previous study, fluorescently labeled BPGs were injected intra‐articularly in a rabbit knee joint in vivo model and BPG diffusion through cartilage was observed (Phillips et al, ). The intra‐articular injection of BPGs resulted in the diffusion of BPGs into and throughout the cartilage, localizing within the PCM.…”
Section: Introductionmentioning
confidence: 99%